An Optimal Energy Management System for PV/Battery Standalone System - Vellanki Mehar Jyothi; T. Vijay Muni; S V N L Lalitha (Institute of Advanced Engineering and Science, 2016)
This paper presents an optimal energy management for PV/battery stand-alone system. The system comprises photovoltaic array, battery, inverter and AC loads. PV array is an uncontrollable source due to the variations in irradiations and temperature. To deliver the highest point to the load a maximum power point tracking technique is used. In synchronization with battery bank the system becomes controllable. Modes of operation of the system are defined by the battery bank. Modes of operation are based on the difference between supply and load demand. This paper project proposes an optimal energy management strategy to improve the performance of the PV system. The anticipated system performance is evaluated for varying loads in MATLAB/simulink.